A study on the transformation of marriage in Botswana - Mathafein, Tshepo Pam (My University, 2019)
Marriage is a social, cultural and legal institution that establishes a union between a man and a woman to start a family and raise children. Before Tswana society had contact with the European missionaries in the 19th century, practices like polygamy, bogadi (bride wealth) and go batlela mosadi (to choose a wife for the man) were highly respected and practiced. The introduction of Christian reforms by the missionaries altered these practices even though they are still practised today. Since the 20th century, the global society has become more interconnected, exchanged ideas and culture as a result of globalisation. Consequently, Botswana's economy, social institutions and cultural traditions have been affected. Some studies argue that cultural diversity and traditions have been under threat as a result of globalisation. The aim of this study is to explore the transformation of marriage in Botswana. A mixed secondary research method of data collection is employed to analyse the changes that the institution of marriage has gone through over the years; the narratives about marriage in modern day Botswana; the contemporary influences of globalisation on marriage and the trends in marriage. In this study, the results indicate that the labour migration in the 1940s-1970s had a significant impact on Botswana's social and economic structure. An increase in educational attainment and career opportunities for women meant more participation in the labour market in Botswana. As a result, people delayed getting married, the number of cohabiting couples increased as well as the divorce cases. The study highlights concerns regarding the effects globalisation is having on the traditions, practices and values of Tswana marriage.

Evlilik, bir erkekle bir kadın arasında bir aile kurmak ve çocuk yetiştirmek için bir birlik kuran sosyal, kültürel ve yasal bir kurumdur. Botsvana'da, Tswana toplumunun 19. yüzyılda Avrupalı misyonerler ile temasa geçmesinden önce, çok eşlilik, bogadi (başlık parası) ve go batlela mosadi (erkek için bir eş seçmek) gibi uygulamalar uygulanırdı ve onlara çok saygı duyulurdu. Bugün hâlâ uygulanmakta olsalar bile, misyonerler tarafından başlatılan Hristiyan reformları, bu uygulamaları değiştirdi. 20. yüzyıldan bu yana, küresel toplum daha iç içe geçmiş bir hale geldi ve küreselleşme sonucunda fikir ve kültür alışverişinde bulundu. Sonuç olarak, Botswana'nın ekonomisi, sosyal kurumları ve kültürel gelenekleri bu süreçlerden etkilendi. Bazı araştırmalar, küreselleşme sonucunda kültürel çeşitliliğin ve geleneklerin tehdit altında olduğunu savunuyor. Bu çalışmanın amacı Botswana'da evliliğin dönüşümünü araştırmaktır. Evlilik kurumunun yıllar içinde geçirdiği değişiklikleri, günümüzde Botswana'da evlilikle ilgili anlatıları, küreselleşmenin evlilik üzerindeki etkilerini ve bu alandaki eğilimleri analiz etmek için karma bir ikincil veri toplama yöntemi kullanılmıştır. Bu çalışmada, sonuçlar 1940'lar ve 1970'ler arasındaki emek göçünün Botswana'nın sosyal ve ekonomik yapısı üzerinde önemli bir etkisi olduğunu göstermektedir. Daha fazla kadının eğitim almaya başlaması ve kadınların kariyer fırsatlarındaki artış, Botswana'da kadınlar için iş gücü piyasasına daha fazla katılım anlamına geldi. Sonuç olarak, insanlar evlenmeyi geciktirdi, boşanma vakalarının yanı sıra birlikte yaşayan çiftlerin sayısı da arttı. Bu çalışma, küreselleşmenin Tswana evliliğinin gelenekleri, uygulamaları ve değerleri üzerindeki etkileriyle ilgili endişelerin altını çizmektedir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Marriage; Globalization; Transformation; Africa; Botswana